Crystal structure of 8-(trifluoromethyl)imidazo[1,2-a]pyridine-3-carbaldehyde, C9H5F3N2O - You Gui-Rong (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C9H5F3N2O, orthorhombic, Pnma (no. 62), a = 7.276(2) Å, b = 6.7773(19) Å, c = 17.613(5) Å, V = 868.5(4) Å3, Z = 4, Rgt(F) = 0.0399, wRref(F2) = 0.1122, T = 293(2) K.